Impact of Vortioxetine on severity, cognitive dysfunctions, and functionality in patients with major depression: a real world experience from Pakistan - Minhas, Fareed Aslam; Rusham Zahra Rana; Hamdani, Syed Usman; Mowadat Hussain Rana (Journal of Pakistan Psychiatric Society, 2021)
PREVIDA stands for Pakistani study on Real world Evidence with Vortioxetine in major Depression in Asia. Anywhere in the world, a clinician’s and a patient’s real-world experience with antidepressant treatment is expected to take place minimally in the following spheres: Impact on severity of depression. Improvement in functioning at cognitive level, work performance, and productivity. Safety and tolerability Treatment adherence Cost of treatment In the PREVIDA study we have studied the performance of vortioxetine as a medication intervention in depression on all of the above spheres across Pakistan on almost 500 patients. The manufacturers provided the drug to patients free of cost over three months.